Caracterización fisicoquímico y cromatográfica del aceite esencial de las hojas de Eryngium foetidum L. (sacha culantro) - Canayo Tello, Apeles Perickles Teoklio (2023)
Eryngium foetidium of the Apiaceae family is used as a condiment in the preparation of food in the regional Amazonian cuisine. in addition, because it possesses bioactive molecules, it is used in traditional medicine as an antiflatulent, antibacterial, antipyretic, analgesic, anti-influenza, and antinociceptive. This study aimed to characterize the essential oil extracted from E. foetidium leaves by hydrodistillation in a Karlsruhe apparatus. It was characterized by the determination of physicochemical properties and by gas chromatographic analysis coupled to a mass spectrometer, giving the following results: density 0.8686 g/cm3, refractive index 1.456 and the color reaction for aldehydes and esters gave a yield of 0.107%. By GC-MS analysis, 6 components were identified which in order of abundance 2-Dodecanal is 58.13%, Hexadecanoic acid ethyl ester 16.82%, unknown (C14H26O) 11.12%, and Nonadecane 6.86%., The essential oil of E. foetidum from the Peruvian Amazon because it contains 58.13% 2-dodecanal, in addition to its use in cooking as a seasoning, may have greater application in the pharmaceutical industry for its anthelmintic, antibacterial, and fungicidal properties of these aldehydes, being another important option that can be applied in cosmetics to make toilet soaps and finally as an ecological fuel.